Determination of Stability Constants of Some Metal Mixed Complexes in Solution by Solution Electophoresis [Be(II), Mn(II), Pb(II), Cd(II)-Methyl Cysteine-NTA System] - KUMAR YADAV, TARUN; SINGH, SATYENDRA (Asian Journal of Chemistry, 2010)
An innovative solution electrophoresis technique has been used for the study of mixed ligand complexes of some divalent metals ions viz., Be(II), Mn(II), Pb(II) and Cd(II) with methyl cysteine as primary ligand and NTA as secondary ligand. The stability constants of the mixed complexes formed were found to be: 4.81, 4.67, 3.54, 3.65 (log k values) for Be(II), Mn(II), Pb(II) and Cd(II), respectively at 30 ± 0.5 ºC an ionic strength 0.1 M.